Análise da evolução e aplicação do direito na tutela do meio ambiente - Senise, Walter José (2009)
The present research work analyses the evolution of the law and its efficacy to the environmental protection, considering the character of the environmental law as the main Diffuse Right - consequently the environmental law requires a Diffuse treatment, no more linked with the private law traditional instruments